Characterization Of Malaysian Isolates Of Bovine Herpes Virus I Of Buffalo Origin - Cheow, Loretta Marie (1992)

(untitled)
This research was carried out to investigate two isolates of bovine herpes virus I (BHV -l) isolated from buffaloes at Universiti Pertanian Malaysia , Serdang , Selangor Darul Ehsan, and compare them to a reference cattle strain of BHV- l ( Cooper strain) . The cytopathogenic and serologic properties of the three virus isolated (Buffalo respiratory , Buffalo genital , and the Cooper strain) were first studied. The cytopathogenicity of the three BHV-1 isolates was investigated using Acridine Orange staining (to compare localization of DNA) , Hematoxylin and Eosin staining (to compare morphologic changes induced in cell culture), the indirect Immunoperoxidase ( lIP) staining method ( to compare localization o f the virus antigen ) , plaque assay, and Negative Contrast Electron Microscopy.